Characteristics of intimate partner violence victimization experienced by a sample of portuguese men - Machado, Andreia (2018)
International research has established that men can be victims of intimate partner violence(IPV). In Portugal, this phenomenon has not yet received scientific or social attention,although since the 1990s, IPV has been acknowledged as a notable problem. An onlinecross-sectional study was conducted with 89 heterosexual men who, after completing theRevised Conflict Tactics Scales, identified themselves as victims of IPV. We examined theprevalence of IPV, its context, its perceived impact, men's reactions after an episode ofviolence, men's perceived motives for the partner's aggressive behavior, and reasons thatprevented men from leaving the abusive relationship. The results revealed many similaritiesto the findings in the literature on female victims and are discussed in terms of theirpractical implications. Increased knowledge of this underreported phenomenon is vital tothe development of suitable policies and support services.